IMPLEMENTASI KEBIJAKAN PENINGKATAN INDEKS PERTANAMAN (IP) PADI DI KABUPATEN TANAH DATAR - Hafiszah, Lutfiah; Yusran, Rahmadani (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to analyze the implementation of the Cropping Index (CI) improvement policy in Tanah Datar Regency using Winter’s Integrated Implementation Model (1999; 2012). The model highlights the interconnection between four core dimensions of policy implementation: policy design, organizational behavior, implementer behavior, and target-group behavior. This research employed a qualitative approach through in-depth interviews, field observations, and policy document analysis. The results reveal a gap between the normative policy design and the actual implementation capacity at the local level. The Department of Agriculture and Agricultural Extension Centers have demonstrated institutional commitment but still face challenges related to resource limitations, coordination mechanisms, and the workload of field extension officers. Conversely, implementers exhibit adaptive and innovative behavior in mediating policy goals with farmers’ realities, while target groups actively participate by negotiating and localizing policy according to their social and cultural values. The study concludes that the success of the Cropping Index policy is relational, depending on the dynamic interaction between the state and society. Theoretically, this research expands the application of Winter’s Model to the agricultural policy context in Indonesia, while empirically it provides novelty by identifying social and institutional adaptation practices that shape the effectiveness of agricultural policy at the village level.